Mosty mostite Studi in onore di Marcello Garzaniti - Alberti, Alberto; Ferro, Maria Chiara; Romoli, Francesca (Biblioteca di Studi Slavistici, 2016)
This volume intends to pay homage to Marcello Garzaniti on the occasion of his 60th birthday and thirtieth anniversary of his career, in recognition of his generous commitment in the field of research, popularisation of science and teaching. The heterogeneity of the contributions offered by colleagues, students and friends testifies to the scholar's erudition and multifaceted interests. The five sections composing the volume range from the history of culture to the history of the Slavic ecclesiastical literary civilisation, from linguistics to Slavic literature, without neglecting the history of Slavistics. The volume is completed by the bibliography of the scientific production of Marcello Garzaniti.